Synthetic consortia of nanobody‐coupled and formatted bacteria for prophylaxis and therapy interventions targeting microbiome dysbiosis‐associated diseases and co‐morbidities. Issue 1 (21st December 2018) - Timmis, Kenneth; Timmis, James Kenneth; Brüssow, Harald; Fernández, Luis Ángel
Abstract : Designed nanobody‐linked synthetic consortia for microbiota dysbiosis therapies. A. Nanobodies (Nb) are selected for specific antigens on target bacteria destined for a synthetic therapy consortium that may consist of two (B) or multiple (C) members. For the treatment of dysbiosis co‐morbidities requiring two functionally distinct consortia, these may be linked through a common member to generate a single bi‐functional microbiota therapy (D).